Investigating methodologies for evaluating the effectiveness of Integrated Spatial Information System (ISIS) implementation in the valuation department of the City of Cape Town - Leponesa, Mphepelo Mabesa (School of Architecture, Planning and Geomatics, 2015)
Includes bibliographical references.